Body composition and functional limitation in COPD - Eisner, Mark D (BioMed Central, 2007)
BACKGROUND: Low body mass index has been associated with increased mortality in severe COPD. The impact of body composition earlier in the disease remains unclear. We studied the impact of body composition on the risk of functional limitation in COPD. METHODS: We used bioelectrical impedance to estimate body composition in a cohort of 355 younger adults with COPD who had a broad spectrum of severity. RESULTS: Among women, a higher lean-to-fat ratio was associated with a lower risk of self-reported functional limitation after controlling for age, height, pulmonary function impairment, race, education, and smoking history (OR 0.45 per 0.50 increment in lean-to-fat ratio; 95% CI 0.28 to 0.74). Among men, a higher lean-to-fat ratio was associated with a greater distance walked in 6 minutes (mean difference 40 meters per 0.50 ratio increment; 95% CI 9 to 71 meters). In women, the lean-to-fat ratio was associated with an even greater distance walked (mean difference 162 meters per 0.50 increment; 95% CI 97 to 228 meters). In women, higher lean-to-fat ratio was also associated with better Short Physical Performance Battery Scores. In further analysis, the accumulation of greater fat mass, and not the loss of lean mass, was most strongly associated with functional limitation among both sexes. CONCLUSION: Body composition is an important non-pulmonary impairment that modulates the risk of functional limitation in COPD, even after taking pulmonary function into account. Body composition abnormalities may represent an important area for screening and preventive intervention in COPD.